2011
DOI: 10.1523/jneurosci.2605-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Interindividual Differences in Children's Audiovisual Speech Perception

Abstract: Children use information from both the auditory and visual modalities to aid in understanding speech. A dramatic illustration of this multisensory integration is the McGurk effect, an illusion in which an auditory syllable is perceived differently when it is paired with an incongruent mouth movement. However, there are significant interindividual differences in McGurk perception: some children never perceive the illusion, while others always do. Because converging evidence suggests that the posterior superior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 92 publications
(106 reference statements)
4
78
2
Order By: Relevance
“…ba 83 13 ba 92 8 pa 83 0 pa 75 0 Visual da 8 29 ga 0 0 ka 0 4 ta 25 96 Fusion and others ta 0 46 da 8 50 ta 17 75 ha 0 4 pa 8 8 ta 0 42 a 0 17 ga 0 4 The McGurk effect in older children with CI may stem from a more mature audiovisual integration. Nath et al also observed audiovisual integration beginning around 6 years of age [15]. Although audiovisual integration involved in the McGurk effect did not appear in normal-hearing Japanese children probably due to language simplicity [20], older children with CI who hear artificial and insufficient speech sounds coded by CI might use more visual information to compensate for hearing difficulties.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…ba 83 13 ba 92 8 pa 83 0 pa 75 0 Visual da 8 29 ga 0 0 ka 0 4 ta 25 96 Fusion and others ta 0 46 da 8 50 ta 17 75 ha 0 4 pa 8 8 ta 0 42 a 0 17 ga 0 4 The McGurk effect in older children with CI may stem from a more mature audiovisual integration. Nath et al also observed audiovisual integration beginning around 6 years of age [15]. Although audiovisual integration involved in the McGurk effect did not appear in normal-hearing Japanese children probably due to language simplicity [20], older children with CI who hear artificial and insufficient speech sounds coded by CI might use more visual information to compensate for hearing difficulties.…”
Section: Discussionmentioning
confidence: 97%
“…The age of 6 years was chosen as the cutoff point because at this age the McGurk effect appears in native speakers of European languages [7,20] and audiovisual integration in STS also begins to function [15]. Children's perception of facial expressions also improves between 5 and 10 years of age [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first is the well-known SLF/AF pathway that anchors the dorsal stream and is thought to be involved in phonological processing, receptive and expressive language processing, and literacy. The second pathway is the newly described (Bahrick, Lickliter, & Flom, 2004;Blomert & Froyen, 2010;Erdener & Burnham, 2013;Gogate & Bahrick, 1998;Gogate, Bahrick, & Watson, 2000;Lachs, Pisoni, & Iler Kirk, 2001;Magnan & Ecalle, 2006;Magnan, Ecalle, Veuillet, & Collet, 2004;Nath, Fava, & Beauchamp, 2011;Ross et al, 2011;Sekiyama & Burnham, 2004). For example, amodal information, which refers to information shared across multiple sense modalities (i.e., temporal synchrony, rhythm, tempo), seems to have the effect of directing attention to what is important in the environment, and enhancing salient features of actions and objects Calvert, Campbell, & Brammer, 2000).…”
Section: Fiber Pathways For Speech Language and Literacymentioning
confidence: 99%
“…The first, the sensory-sensory (auditory-visual) pathway is anchored by the posterior superior temporal sulcus (STSp), and connects visual domains (especially MT/V5), primary auditory cortex, STSp, and inferior frontal regions (Arnal, Morillon, Kell, & Giraud, 2009;Calvert, 1997). Evidence in older children (Nath & Beauchamp, 2012;Nath et al, 2011) and adults (Arnal et al, 2009;Barrós-Loscertales et al, 2013;Calvert, 1997) and auditory stimuli (e.g., visual /da/, auditory /ba/), and as a consequence report hearing a syllable that is different from the original stimuli (e.g., ga).…”
Section: Neural Components Of Speech Several Brain Regions Have Beenmentioning
confidence: 99%